Efektivitas Diplomasi Haji oleh Kementerian Agama Indonesia pada Tahun 2020-2023 - Renta, Pebria Prakarsa; Trisnani, Endah; Sallimi, Hadidah; Surwandono, Surwandono (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2023)
This research aims to explain the effectiveness of Hajj diplomacy carried out by the Indonesian Ministry of Religion (KEMENAG) in resolving various problems of Indonesian Hajj pilgrims based on Law Number 8 of 2019 concerning the Implementation of the Hajj and Umrah Pilgrimage. This research uses the concept of Hajj Diplomacy. Based on the results of this research, it can be seen that the actions taken by the Indonesian Ministry of Religion in overcoming Hajj problems are quite significant as evidenced by several things, namely cooperation with Saudi Arabia to obtain additional quotas from other countries, the Minister of Religion ensuring the preparation of Hajj services in Saudi Arabia, the Ministry of Religion optimizing functions Head of the group and team leader in the process of carrying out the Hajj, the Ministry of Religion is developing a reporting system for the implementation of Android-based worship guidance and the Ministry of Religion will also field a team of Hajj Consultants. Therefore, through these results it can be concluded that the Hajj diplomacy carried out by the Indonesian Ministry of Religion in 2020-2023 has been quite effective as proven by being able to implement Law Number 8 of 2019 concerning the Implementation of the Hajj and Umrah Pilgrimage Article 29 paragraph (1) and (2).